The cognitive effects of al-qur’an memorization: a systematic review of impacts on memory, academic performance, and broader cognitive functions - Novianita Achmad; Sarson W. Dj. Pomalato; Maryam Rahim; Novianty Djafri; Evi Hulukati (Jurnal Konseling dan Pendidikan, 2025)
This systematic review critically synthesizes 30 empirical studies to evaluate the cognitive consequences of Al-Qur'an memorization (hifdh), addressing a significant gap in differentiating between domain-specific memory gains and broader cognitive enhancement. Utilizing a rigorous selection process from the Semantic Scholar corpus, the study examines the impact on core memory functions, the potential for transfer to academic and executive domains, and the efficacy of various pedagogical interventions. The results demonstrate compelling evidence for "near transfer," where intensive memorization reliably enhances short-term, episodic, and verbal memory. However, the evidence for "far transfer" to general intelligence or non-memory domains remains mixed; while quasi-experimental studies suggest positive academic correlations, methodologically robust controlled trials indicate that these skills are highly domain-bound. The review also highlights that structured, technology-assisted pedagogical methods significantly outperform traditional rote approaches. A key novelty of this work is the identification of a "reverse replication crisis," revealing that the field is characterized by methodological homogeneity and geographical concentration, primarily in Indonesia, which may inflate positive findings. These insights offer vital practical implications, suggesting that while educators can leverage hifdh for specific memory training, they should exercise caution regarding claims of general cognitive improvement. Ultimately, this study contributes a nuanced framework for understanding religious memorization practices, advocating for a shift toward randomized controlled trials to establish clearer causal links in educational neuroscience.